Islamic Religious Education in Corruption Prevention at Public Universities in East Kalimantan - Khojir Khojir; Agus Setiawan; Siteehaya Maboh (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The purpose is to find out the policies of general universities in preventing corruption, analyze the development of Islamic Religious Education materials in preventing corruption, analyze the methods of Islamic Religious Education learning and preventing corruption and find out the evaluation of learning and its impact on preventing corruption in general universities in East Kalimantan. This research is qualitative with a phenomenological-pedagogical approach. The data sources are university leaders, Islamic Religious Education lecturers and students. Data collection was carried out through interviews, observations and documentation. Data analysis used the Milles and Huberman model assisted by Nvivo 12 software. The results of this study are 1) The policies of general universities in preventing corruption are opening one-door cooperation, accountability for activities through reports, prohibition of gratification, Islamic Religious Education based on anti-corruption, forming an anti-corruption task force, forming an SPI, implementing statutes properly, providing an Anti-Corruption Education MK and unification of accounts. 2) Development of Islamic Religious Education material containing corruption prevention, namely the implementation of the pillars of faith and the pillars of Islam, honesty, trust, development of faith and piety material, honesty-based transactions, honest agricultural products, discussion of corruption in an Islamic perspective, modern shirk. 3) Islamic Religious Education learning methods in preventing corruption include lectures, questions and answers, discussions, consistent with lecture contracts, peer studies, assignments (structured and independent), projects. 4) The types of evaluations used in preventing corruption are mid-term exams, final exams, observations, project assessments, FGDs, identification of commendable and uncommendable attitudes in lectures and reflections.